Drug therapy for atrial fibrillation: quo vadis? - Jardine, Ronald M. (SA Heart Journal, 2017)
Atrial fibrillation has always been the most common sustained cardiac arrhythmia, and its incidence is increasing worldwide. Despite evolving ablation techniques, the vastness of the number of cases entrenches drug therapy as the mainstay of treatment for the majority of cases both now and in the foreseeable future. Drug therapy for atrial fibrillation includes drugs for ventricular rate control, anti-coagulation, and cardioversion/maintenance of sinus rhythm (rhythm control). This review summarizes the available data on new drugs in each of these 3 areas. In the area of rhythm control, it is clear that primary prevention of atrial fibrillation is achieved by a number of drugs in common clinical usage in hypertension, heart failure, and vascular disease, viz. blockers of the renin-angiotensin system and statins. Primary prevention is also promising with novel therapies such as anti-inflammatory therapy, pirfenidone, and Ω-3 poly-unsaturated fatty acids. Secondary prevention with anti-arrhythmic drugs producing multiple channel blockade is proven to be efficacious, and atrial-selective anti-arrhythmic drugs are an attractive development and will avoid ventricular pro-arrhythmia. A number of new drugs with novel mechanisms of action have mostly not yet undergone clinical trials, but are discussed here, and include gap junction modulators, stretch-activated channel blockers, sodium-calcium exchange inhibitors and new ion channel blockers.